Seychelles : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This Selected Issues paper for Seychelles argues that sound fiscal policies and smaller governments can be conducive to growth and help reduce a country's economic vulnerability. Growth in Seychelles has been volatile and underperformed most small states from 1998 to 2005. Seychelles's revenues, expenditures, and total public debt are higher after an improvement in 2003. Its fiscal balance has worsened and has been weaker in comparison with most small states for most of the period. Seychelles's expenditure composition is most similar to that of low-growth small states.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet